PENGARUH INFORMASI HOAX TERHADAP KONFLIK PADA REMAJA DI SOSIAL MEDIA - Mira Herlina; Rocky Prasetyo Jati (Jurnal Ilmu Komunikasi AKRAB, 2018)
This research is motivated because lately Indonesia hoax information is very developed in Indonesia so that hoaxes can trigger conflict in people who are active in using Social Media, especially teenagers, Teenagers are very active using social media such as Instagram, Tweeter, Facebook, and Whatsaap Group and Other social media This study aims to determine how much influence hoax information has on the level of conflict in adolescents on social media. This study uses an explanatory quantitative method using a population of adolescents in West Jakarta totaling 97 Respondents of Variable X this study uses concepts related to information Hoax and the concept of conflict is used to measure the variable Y. This study found that there was a significant effect on variable X namely Hoax information on Y variable is conflict in adolescents on social media. The hoax information variable contains more fanaticism and the spread of ideology because this indicator is in a very high category, while the variebles of conflict between personal and intra-personal conflict indicators are higher, and fanaticism and ideological conflict variables are the causes of conflict which are in the high category , so that this study concludes the need for a legal arrangement that regulates content spread in social media and the need for literacy for adolescents as a strategy to reduce adolescent conflict on social media because of hoaxes that cause conflict in adolescents.